2017
DOI: 10.18697/ajfand.80.16280
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity and nutrient intake adequacy among women in Iwo local government area, Osun State Nigeria

Abstract: Dietary diversity has been considered a potential 'proxy' indicator to reflect nutrient intake adequacy. The study assessed the Dietary Diversity and Nutrient Intake Adequacy among adult women in Iwo Local Government (LGA) area of Osun State. Apparently healthy 250 adult women were the respondents in the study. The anthropometric measurements of the respondents were taken using standard equipment. A 24-hour dietary recall questionnaire was used to assess the food intake of the respondents, which was converted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(28 reference statements)
0
3
1
Order By: Relevance
“…Darboux et al, 2022 on Assessment of the nutritional status and dietary intake of women of childbearing age in the city of Comè, Benin.The minimum dietary diversity for women score showed that majority (71.3%) of the respondent had a low dietary diversity score and 28.2% of the respondents had a minimum dietary diversity score. It has been demonstrated that dietary variety scores are reliable and affordable markers for evaluating nutritional quality at the population level(Oladoyinbo et al, 2017). This study's mean DDS (3.92) was lower than the mean DDS reported by earlier research.…”
contrasting
confidence: 77%
“…Darboux et al, 2022 on Assessment of the nutritional status and dietary intake of women of childbearing age in the city of Comè, Benin.The minimum dietary diversity for women score showed that majority (71.3%) of the respondent had a low dietary diversity score and 28.2% of the respondents had a minimum dietary diversity score. It has been demonstrated that dietary variety scores are reliable and affordable markers for evaluating nutritional quality at the population level(Oladoyinbo et al, 2017). This study's mean DDS (3.92) was lower than the mean DDS reported by earlier research.…”
contrasting
confidence: 77%
“…Dietary guidelines worldwide have promulgated the benefits of a variety of dietary intake, mainly because it is easier to provide the necessary amount of nutrients with a highly diverse diet. This could be especially important for obesity and chronic disease management [47,48]. In this regard, monotonous diets usually imply unhealthy eating habits, as well as the worsening in the progression of certain diseases, for example CVD [49].…”
Section: Discussionmentioning
confidence: 99%
“…The mean adequacy ratio (MAR) was computed as a proxy for su cient nutrient intake of the population. The mean ARs were calculated for eleven micronutrients: zinc, thiamine, niacin, ribo avin, calcium, iron, vitamin A, vitamin B6, vitamin C, vitamin B12, and folate (Adebukola et al, 2017). The real NAR values were truncated at 1 in the MAR computation, meaning that a nutrient with a high NAR could not compensate for a nutrient with a low NAR (Adebukola et al, 2017).…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…The mean ARs were calculated for eleven micronutrients: zinc, thiamine, niacin, ribo avin, calcium, iron, vitamin A, vitamin B6, vitamin C, vitamin B12, and folate (Adebukola et al, 2017). The real NAR values were truncated at 1 in the MAR computation, meaning that a nutrient with a high NAR could not compensate for a nutrient with a low NAR (Adebukola et al, 2017). NAR = (Nutrient intake ÷ Recommended intake) NAR = (Nutrient intake ÷ Recommended intake) × 100%…”
Section: Data Collection Toolsmentioning
confidence: 99%